Optimal design and dynamic performance analysis of a fractional-order electrical network-based vehicle mechatronic ISD suspension - Shen, Yujie; Hua, Jie; Fan, Wei; Liu, Yanling; Yang, Xiaofeng; Chen, Long (Mechanical systems and signal processing, 2023)
[Display omitted] •A novel optimal design methodology of vehicle mechatronic ISD suspension using the fractional-order electrical network is proposed, to enhance the vibration suppression performance.•The correspondingrelationship and analytical expression between the fractional-order mechanical network elements and the fractional-order electrical network elements are obtained.•A quarter car is taken as an example, the dynamic model of the vehicle mechatronic ISD suspension using the fractional-order electrical network and the integer-order network are established.•The advantages of the vehicle mechatronic ISD suspension using the fractional-order electrical network are validated through numerical simulations and experiments under different road input conditions. To further explore the beneficial effects of the vibration isolation performance of a new vehicle ISD (inerter-spring-damper) suspension using a mechatronic inerter, this paper proposes a novel optimal design methodology for a vehicle mechatronic ISD suspension system based on a fractional-order electrical network is proposed. In view of difficulties in the engineering implementation of fractional-order mechanical network elements, this paper first studies the correspondingrelationship and analytical expression of fractional-order mechanical and electrical network elements respectively. Under the instruction of fractional calculus, the fractional-order electrical network elements are used to realize equivalent fractional-order mechanical network elements by adopting a ball-screw mechatronic inerter. Then, a quarter car dynamic model of vehicle mechatronic ISD suspension is constructed, and the parameters of the fractional-order electrical network and the integer-order electrical network are obtained by means of particle swarm optimization algorithm. The performance advantages of vehicle mechatronic ISD suspension using a fractional-order electrical network are verified by numerical simulations and experiments. The results show that, compared with the application of an integer-order electrical network, the vibration suppression performance of a vehicle mechatronic ISD suspension can be further enhanced by using a fractional-order electrical network.